Can the aqueous decoction of mango flowers be used as an antiulcer agent? - Lima, Z. P.; Severi, J. A.; Pellizzon, C. H.; Brito, ARMS; Solis, P. N.; Caceres, A.; Giron, L. M.; Vilegas, Wagner [UNESP]; Hiruma-Lima, C. A. (Elsevier B.V., 2006)
This study was designed to determine the effect of Mangifera indica flowers decoction, on the acute and subacute models of induced ulcer in mice and rats. A single oral administration of the aqueous decoction (AD) from M. indica up to a dose of 5 g/kg, p.o. did not produce any signs or symptom of toxicity in the treated animals. The oral pre-treatment with AD (250, 500 and 1000 mg/kg) in rats with gastric lesions induced by ethanol, decreased the gastric lesions from 89.0 +/- 6.71 (control group) to 9.25 +/- 2.75, 4.50 +/- 3.30 and 0, respectively. Pretreatment with AD (250, 500 and 1000 mg/kg) to mice with HCl/ethanol- or stress-induced gastric lesions resulted in a dose-dependent significant decrease of lesion index. In the piroxicam-induced gastric lesions, the gastroprotective effect of AD was reducing with the increase of the AD dose. In the pylorus-ligature, AD (p.o.) significantly decreased the acid output indicating the antisecretory property involved in the gastroprotective effect of M. indica. Treatment with AD during 14 consecutive days significantly accelerated the healing process in subacute gastric ulcer induced by acetic acid in rats. Pretreatment with N-nitro-L-arginine methyl ester (L-NAME), an inhibitor of NO-synthase, did not abolish the gastroprotective effects (99% with saline versus 80% With L-NAME) of AD against ethanol-induced gastric lesions. Pretreatment with N-ethylmaleimide (NEM), a blocker of endogenous sulphydryl group, significantly abolished the protective effects of AD against ethanol-induced gastric ulcers (95% with saline versus 47% with NEM). Phytochemical screening showed the presence of steroids, triterpenes, phenolic compounds and flavonoids. Estimation of the global polyphenol content in the AD was performed by Folin-Ciocalteu method and showed approximately 53% of total phenolic on this extract. These findings indicate the potential gastroprotective and ulcer-healing properties of aqueous decoction of M. indica flowers and further support its popular use in gastrointestinal disorders in Caribbean. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: Mangifera indica; flowers; Anacardiaceae; gastric antiulcer; healing effect